STUDIES REGARDING THE STATIC ANALYSIS OF TRUSS STRUCTURES - URDEA Mihaela (Journal of Industrial Design and Engineering Graphics, 2017)
This paper refers to linear static analysis of truss and beams structures modelled in SolidWorks. In SolidWorks truss and frame elements are available only for staticstudies. For illustration it was modelled and studied the behaviour of a support of pipe. The truss is a welded structure modelled with Weldment Structural Members and it is often found in industrial constructions. During this study, there have been investigated the following FEA steps: Pre-Processing, Processing and Post-Processing.The results of this study are images corresponding to Axial Stress and The Maximum Displacement in different situations.